2018
DOI: 10.1055/s-0038-1660434
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Pattern of Maxillofacial Injuries Caused by Motorcycle Crashes Presenting at Two Major Referral Hospitals in Nairobi, Kenya

Abstract: Motorcycle crashes in Kenya have increased over the last decade and the most common injuries include the cranio-maxillofacial regions which needs documentation. This article determines the occurrence and pattern of maxillofacial injuries in motorcycle crashes. This was a descriptive, cross-sectional prospective study conducted at two referral hospitals in Nairobi, Kenya. Data were obtained through interview and physical examination of patients. Ninety-one patients were examined, among whom 76 (83.5%) were male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…In other studies, only 10% of the casualties had consumed alcohol. 19 the relatively high percentage of alcohol victims in our study may be due to the small sample size.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In other studies, only 10% of the casualties had consumed alcohol. 19 the relatively high percentage of alcohol victims in our study may be due to the small sample size.…”
Section: Discussionmentioning
confidence: 72%
“…These factors are similar to those previously considered by studies from India. 14,19 In contrast, studies from Kenya 20 and Tanzania 17 reported that most of the motorcycle collisions occur during the day and less at night (62.6% and 73.9%, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…20 Lack of adequate training coupled with poor law enforcement among motorcyclists may be the reason of the accidents. 21 The number of lower face fractures was more in the nonfastened group. This was statistically significant (p < 0.001).…”
Section: Discussionmentioning
confidence: 87%
“…After the application of the compulsory helmet law, which states mandatory helmet use for the rider as well as the pillion, the incidence of maxillofacial injuries as well as traumatic brain injuries has reduced considerably 20. Lack of adequate training coupled with poor law enforcement among motorcyclists may be the reason of the accidents 21…”
Section: Discussionmentioning
confidence: 99%
“…Boda boda accidents are frequent owing to risky riding behaviours such as riding while under the influence of alcohol and drugs, poor maintenance of motorcycles and low levels of professional training (Nyachieo, 2015;Nguyen et al, 2018). Boda boda traffic accident related deaths and injuries have become major public health epidemics in Kenya (Nyameino, 2018).…”
Section: Introductionmentioning
confidence: 99%